2022
DOI: 10.2106/jbjs.21.01387
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning and Imaging for the Orthopaedic Surgeon

Abstract: ä In the not-so-distant future, orthopaedic surgeons will be exposed to machines that begin to automatically "read" medical imaging studies using a technology called deep learning.ä Deep learning has demonstrated remarkable progress in the analysis of medical imaging across a range of modalities that are commonly used in orthopaedics, including radiographs, computed tomographic scans, and magnetic resonance imaging scans.ä There is a growing body of evidence showing clinical utility for deep learning in muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(79 reference statements)
0
4
0
Order By: Relevance
“… 21 AI has already shown the potential for impacts in orthopedics beyond writing such as the creation of outcome prediction algorithms in trauma, imaging interpretation, and extraction of data from electronic health records. 3 , 14 , 20 , 26 , 27 Importantly, the ChatGPT interface specifically discloses that the AI system may occasionally generate incorrect or harmful content, and our study found that the responses consistently recommend speaking to an orthopedic surgeon for diagnosis and treatment. Regardless, there is an increasingly prevalent call for curtailing the use of AI technology in medicine largely due to its lack of transparency.…”
Section: Discussionmentioning
confidence: 61%
“… 21 AI has already shown the potential for impacts in orthopedics beyond writing such as the creation of outcome prediction algorithms in trauma, imaging interpretation, and extraction of data from electronic health records. 3 , 14 , 20 , 26 , 27 Importantly, the ChatGPT interface specifically discloses that the AI system may occasionally generate incorrect or harmful content, and our study found that the responses consistently recommend speaking to an orthopedic surgeon for diagnosis and treatment. Regardless, there is an increasingly prevalent call for curtailing the use of AI technology in medicine largely due to its lack of transparency.…”
Section: Discussionmentioning
confidence: 61%
“…The limitations of this study is that only MPNN is utilized in the study, other ML methods such as the support vector machines (SVM) [ 39 ] or convolutional neural networks (CNN) [ 35 , 40 , 41 ] have not been investigated to identify if there is a better ML algorithm for building a ML model. The sample size appeared to be small.…”
Section: Discussionmentioning
confidence: 99%
“…Segmentation can be a manual process, but developments in deep learning algorithms have enabled automatic processing, which can be advantageous as it limits inter-and intraobserver variations. 12 For larger datasets, automated processes are often needed because manual techniques are more timeconsuming and less reproducible.…”
Section: What Is Radiomics?mentioning
confidence: 99%